Influence of leadership characteristic towards succession planning program implementation in Malaysia' Public Sector. - Ahmad, Rohana; Mohamed, Ahmad Martadha; Abdul Manaf, Halimah (IWNEST PUBLISHER, 2015)
This paper examines the influence of leadership characteristic style towards succession planning, program implementation in Malaysia’s Public Sector. Four dimensions of leadership characteristic were used, namely idealized influence, inspirational motivation, individualize influence and intellectual stimulation. Combination Multifactor Leadership Questionnaire and effective Succession Planning and Management Questionnaire. A sample of 394 respondents is taken from Malaysia’s Public sector employees. From multiple regression analysis, the result revealed that individualized influence (ß=. 162, p<0.05) is the most influence career development. Keeping in view, the finding of this study provides some practical insight into the need for public sector to re-visit the succession planning and leadership style as these have significant bearing on followers perception. Therefore, with the changing world of work demands and more choice where one size fits one, leaders must able to provide a great characteristic style to balance these with works need to ensure a high level of productivity and performance.